POTENSI BAKTERI KITINOLITIK DALAM PENGENDALIAN Aspergillus niger PENYEBAB PENYAKIT BUSUK PANGKAL AKAR PADA TANAMAN KACANG TANAH - Arifda Ayu; Dwi Suryanto; Isnaini Nurwahyuni (Saintia Biologi, 2012)
A study of chitinolytic bacteria ability to control Aspergillus niger, a causal agent of basal root rot of peanut seedlings was conducted in Pest and Disease Laboratory, Medan Johor and Laboratory of Microbiology, Department of Biology, Faculty of Mathematics and Natural Sciences, University of Sumatera Utara, Medan.  The purpose of study is to evaluate the ability of Bacillus sp. BK13, Enterobacter sp. BK15, Bacillus sp. BK17, Enterobacter cloacae LK08, Bacillus sp. KR05, and Enterobacter sp. PB17 to inhibit the growth of A. niger on the peanut seedling.  Antagonistic test showed that the most effective bacteria in inhibiting the growth of A. niger was BK15 isolate with inhibition zone of 2,88 cm and BK13 isolate with inhibition zone of 2,69 cm, whereas the least effective bacteria was BK17, with inhibition zone of 2,30 cm. Chitinolytic bacterial isolates used to cover peanut seed through soaking enabled to reduce seed basal root rot. BK15 isolate showed potential to reduce the basal root rot by 58,82% while the lowest inhibition was BK13 by 47,06%.   Keywords: Aspergillus niger, Bacillus sp., chitinolytic bacteria, Enterobacter sp., peanut